Mother–offspring recognition via contact calls in cattle, Bos taurus. (April 2016) - Padilla de la Torre, Mónica; Briefer, Elodie F.; Ochocki, Brad M.; McElligott, Alan G.; Reader, Tom
Abstract : Individual recognition in gregarious species is fundamental in order to avoid misdirected parental investment. In ungulates, two very different parental care strategies have been identified: 'hider' offspring usually lie concealed in vegetation whereas offspring of 'follower' species remain with their mothers while they forage. These two strategies have been suggested to impact on mother–offspring vocal recognition, with unidirectional recognition of the mother by offspring occurring in hiders and bidirectional recognition in followers. In domestic cattle, Bos taurus, a facultative hider species, vocal communication and recognition have not been studied in detail under free-ranging conditions, where cows and calves can graze freely and where hiding behaviour can occur. We hypothesized that, as a hider species, cattle under these circumstances would display unidirectional vocal recognition. To test this hypothesis, we conducted playback experiments using mother–offspring contact calls. We found that cows were more likely to respond, by moving their ears and/or looking, turning or walking towards the loudspeaker, to calls of their own calves than to calls from other calves. Similarly, calves responded more rapidly, and were more likely to move their ears and/or look, turn or walk towards the loudspeaker, and to call back and/or meet their mothers, in response to calls from their own mothers than to calls from other females. Contrary to our predictions, our results suggest that mother–offspring vocal individual recognition is bidirectional in cattle. Additionally, mothers of younger calves tended to respond more strongly to playbacks than mothers of older calves. Therefore, mother responses to calf vocalizations are at least partially influenced by calf age. Highlights: We investigated vocal recognition in cattle using playback experiments. Mother–offspring vocal recognition in cattle is a bidirectional process. Calf age is an important factor in determining a cow's response to playbacks. Mothers respond more to playbacks when their calf is younger.